Protective effects of phosphonomethyl-sarcosine against the copper and cadmium induced inhibition of leaf development in poplar - Kovács, Sándor (Acta Biologica Szegediensis, 2005)
Heavy metals can disrupt plant metabolism, including photosynthesis, in a number of different ways. One common mechanism in acclimation of plants to abiotic stresses is the accumulation of compatible solutes. In these study we analysed the effect of exogenously added phosphonomethyl-sarcosine, a derivative of a synthesis intermedier of glycinebetaine, on leaf development in poplar under Cu and Cd stress. While growth was more strongly reduced by Cu treatment, Cd preferably inhibited photosynthesis. These effects were connected to the disturbed water (Cu stress) and ion balance (Cd stress) of plants. The symptoms of Cu and Cd stress were totally and partially abolished by exogenously added phosphonomethyl-sarcosine, respectively. Its protective effect might be based on the complexation of heavy metals (Cu stress), but glycinebetaine-like macromolecule/membrane protecting effects (Cd stress) are also possible.